Quality of life after surgical treatment of breast cancer - Wrażeń, Małgorzata; Wasilewski, Tadeusz Paweł; Michalik, Joanna; Młynarska, Magdalena (Journal of Education, Health and Sport, 2017)
Admission Breast cancer is one of the most common and most serious malignant neoplasms among women. The standard treatment for breast cancer is systemic therapy, which combines surgical treatment with other methods such as radiotherapy, chemotherapy and hormonal therapy. A number of adverse changes that cause these methods in women’s lives violate their balance in all dimensions of human functioning, which in turn affects the quality of life. Purpose of research The main objective of the study was to assess the subjective quality of life among women after surgical treatment of breast cancer. Materials and methods The study included 43 women before surgery, 40 women after surgery and 46 randomized women who were randomly assigned to a control group. Research works were conducted from September to November 2016 at the Center of Oncology in Lublin and Voivodship Specialist Hospital in Lublin. Discussion Breast cancer is the second leading cause of death in women after lung cancer. The standard treatment for breast cancer is systemic therapy, which combines surgical treatment with other methods such as radiotherapy, chemotherapy and hormonal therapy. A number of unfavorable changes that cause these methods in women’s lives violate their balance in all dimensions of human functioning, which in turn affects the quality of life. Conclusions Based on the results of the study, it can be said that the quality of life of chronic patients provides valuable information on their functioning and the side effects of treatment, which in turn can help to improve the level of health services provided and thus the patient’s assessment and satisfaction with care.